Biophysical characterization of the mineral composition of seeds with varying genetic background including transgenic sorghum with reduced amounts of the storage protein kafirin - Roya Janeen Ndimba (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.